(untitled) (CIPEEX, 2022)
SCOLIOSIS IS A POSTURAL CHANGE BEING A LATERAL DEVIATION, WHOSE CHARACTERISTIC IS DEFORMITY IN PARTS OF THE SPINE. IT CAN BE CLASSIFIED AS A THREE-DIMENSIONAL MORPHOLOGICAL DEFORMITY, WHICH CAN CAUSE PROBLEMS. THE PRESENT STUDY AIMS TO EVALUATE THE PREVALENCE OF SCOLIOSIS IN THIRD YEAR HIGH SCHOOL STUDENTS FROM A PRIVATE SCHOOL IN ANÁPOLIS-GO. THIS IS A DESCRIPTIVE, CROSS-SECTIONAL AND QUANTITATIVE FIELD STUDY. IN THE METHODOLOGY, A SOCIODEMOGRAPHIC QUESTIONNAIRE WAS APPLIED AND THE POSTURAL ASSESSMENT WAS CARRIED OUT USING THE SYMMETROGRAPH AND TOGETHER WITH THE POSTURAL ASSESSMENT FORM PROPOSED AND VALIDATED BY LIPOSCKI.D.B; ET AL.2012. THE RESULTS ARE CONSIDERED RELEVANT SINCE MOST STUDENTS HAVE AN AVERAGE AGE OF 17.5, RIGHT-HANDED, SPEND HOURS SITTING, WITH UNEVEN LEFT SHOULDER. THEY PRESENT SCOLIOSIS IN S AND C WITH CONVEXITY TO THE LEFT. WE CONCLUDED THAT DESPITE THE SMALL SIZE OF THE RESEARCH SAMPLE, IT WAS POSSIBLE TO OBSERVE THAT ONLY THOSE STUDENTS WHO HAD COMPLAINTS OR KNEW THEY HAD SOME POSTURAL ALTERATION ACCEPTED TO PARTICIPATE. IT IS CONCLUDED WITH THIS STUDY THAT MOST OF THE EVALUATED ADOLESCENTS PRESENT SOME TYPE OF POSTURAL ALTERATION SUCH AS HYPERLORDOSIS, SCOLIOSIS IN C OR S WITH CONVEXITY TO THE LEFT.